Compression of a line of hard spheres or bubbles in a transverse confining potential - Hutzler, Stefan; Weaire, Denis (Taylor and Francis Group, 2025)
A line of spheres or bubbles, confined in a cylindrically symmetric harmonic potential, buckles under axial compression. Increasing compression results in a sequence of initially planar, and eventually non-planar, structures. We present a catalogue of these, drawing on both experiments and computer simulations. The latter make use of the theory of Morse and Witten to model bubble–bubble interaction. Numerical results are summarised in stability diagrams, of potential relevance to the creation of chiral photonic crystals from self-assembled packings of spheres.
PUBLISHED
Keywords: self-assembly; soft spheres; sphere packings